Optimalisasi Wakaf Di Yordania - Muhammad Riza Aziziy (Jurnal Istiqro, 2018)
This type of research is descriptive research, where the aim is to explain events in the present or the past. This study will present data on the management and development of waqf in Jordan, starting from the formal juridical aspects of the law on representation, the structure of the Ministry of Waqf of Jordan, the role of waqf in economic and social development as well as the potential and obstacles to the development of waqf in Jordan in the future. The result of this study is that the function of the Ministry of Endowments and Islamic Affairs as a regulator in which the coordinative function is attached indirectly encourages the growth of waqf in Jordan, the implementation of programs from the Ministry of Endowments and Religious Affairs there is no definite target of the State every year such as other ministries and utilization of waqf lands have not been widely seen for productive waqf activities.